Model Hubungan Karakteristik Perusahaan dan Pengungkapan Informasi Lingkungan Perusahaan - Lisa Amelia Herman; Srimadona Saleh (JURNAL PUNDI, 2017)
The aims of this study was to determine the effect of company size, profitability and leverage of the corporate Environmental Dislosure (ED). Company size measured by logaritma natural of total asset, profitability measured by return on assets (ROA/ratio of net income to total assets) and leverage measured by debt to equity ratio (DER/ratio of debt to total equity). Corporate environmental disclosure is measured using the environmental indicators from Global Reporting Initiatvive Guidline 4 (GRI G4) with total 34 indicators. This study populations is listed manufacturing companies in Indonesia Stock Exchange in 2013–2015 with total sample of 76 companies. the sampling method was purposive sampling method. The type of data used is secondary data. This study used annual report from listed manufacturing companies in Indonesia Stock Exchange to analyzed. The data was analyzed by using multiple linear regression analysis with IBM SPSS. The result indicate that company size has significant influence to the corporate environmental disclosure. The result for the second and third hypothesis indicated that profitability and leverage has no significant influence to .the corporate environmental disclosure.